2022
DOI: 10.1002/adma.202200929
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Specific Electron‐Driving Observations of CO2‐to‐CH4 Photoreduction on Co‐Doped CeO2/Crystalline Carbon Nitride S‐Scheme Heterojunctions

Abstract: Photoexcited dynamic modulation, maximizing the effective utilization of photoinduced electron–hole pairs, dominates the multiple electrons‐involving reduction pathways for terminal CH4 evolution during CO2 photoreduction. Yet, the site‐specific regulation of directional charge transfer by modification of an S‐scheme heterojunction has seldom been discussed. Herein, an atomic‐level tailoring strategy by anchoring single‐atomic Co into CeO2 co‐catalyst rather than carbon nitride supports, which can selectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(68 citation statements)
references
References 62 publications
2
66
0
Order By: Relevance
“…The in situ FTIR spectra of P25/Pt-KOH displayed in Figure 5c, an absorption peak appeared at 1395 cm À 1 , which was assigned to the asymmetric vibration of surface-adsorbed carbonate (CO 3 2À ) generated by the reaction of adsorbed CO 2 with water molecules on the surface. [29] The intensity of this peak in P25/Pt-KOH was significantly stronger than that in P25/ Pt, implying more CO 2 adsorption in the presence of OH À groups in KOH. Moreover, the 1439 cm À 1 peak could be attributed to the one-electron-reduced COOH*.…”
Section: Chemistry-a European Journalmentioning
confidence: 93%
See 1 more Smart Citation
“…The in situ FTIR spectra of P25/Pt-KOH displayed in Figure 5c, an absorption peak appeared at 1395 cm À 1 , which was assigned to the asymmetric vibration of surface-adsorbed carbonate (CO 3 2À ) generated by the reaction of adsorbed CO 2 with water molecules on the surface. [29] The intensity of this peak in P25/Pt-KOH was significantly stronger than that in P25/ Pt, implying more CO 2 adsorption in the presence of OH À groups in KOH. Moreover, the 1439 cm À 1 peak could be attributed to the one-electron-reduced COOH*.…”
Section: Chemistry-a European Journalmentioning
confidence: 93%
“…Especially, the roles and synergistic effects of two different components of the alkali, i. e., the metal ion and OH À in KOH, have not been thoroughly studied. In addition, it has been reported that metal cocatalysts, [25][26][27][28] such as Pt, [29] could enrich electrons in the catalytic reaction center and enhance the activity of CO 2 photoreduction. Recently, the ability of the Pt co-catalyst to affect the selectivity was also demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…The efficient and selective photocatalytic reduction of CO 2 to methane was achieved through the site regulation of the directed charge transfer of this special S-scheme heterojunction. 150…”
Section: Construction Of Heterojunctionsmentioning
confidence: 99%
“…14(h and i) show the time-resolved transient PL decay and femtosecond transient absorption (fs-TA) spectra of CeCo-PTI, reflecting the decay kinetics of the dynamic charge separation in CeCo-PTI, which reduces the charge recombination ability, and thus improves the catalytic performance. 150 Liu et al designed and synthesized a compound of g-C 3 N 4 and cobalt porphyrin (CoTPP/g-C 3 N 4 ) based on π–π supramolecular interaction, and studied the formation of chemical bonds during CO 2 reduction by in situ Raman testing in saturated CO 2 solution (Fig. 14j).…”
Section: Application In Photocatalytic Co2 Reductionmentioning
confidence: 99%
“…Advanced oxidation processes of semiconductor photocatalysis have been deemed a viable strategy for removing toxic and poisonous compounds owing to their low energy consumption and environmental protection features [ 1 , 2 , 3 ]. Researchers have exploited a variety of efficient photocatalysts in the past to cover the demands, including TiO 2 , ZnO, CeO 2 , CdS, and C 3 N 4 [ 4 , 5 , 6 , 7 , 8 , 9 ]. Among these, bismuth oxychloride (BiOCl) has emerged as one of the most promising photocatalysts in recent years owing to its unique layered structure [Cl-O-Bi-O-Cl] and elastic optoelectronic properties [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%